The role of emotional intelligence in cross-cultural adaptation amongst Iranian students in Malaysia - Mehrabi, Davood; Ali, Muhamad Sham Shahkat (Penerbit Universiti Pertahanan Nasional Malaysia, 2012)
The movement from corner to corner has been an inseparable part of human history. The move into a new culture can be shocking, and internal conflicts may often happen. To avoid of possible conflicts, individuals must learn to adapt and grow into the new environment, as they are often faced with situations that challenge their cultural norms and worldviews. The term cross-cultural adaptation refers to the process in which an individual gets an increasing level of the communication skills from the host culture and of relational development with host nationals. A number of different people may be subject to cross-cultural adaptation; this includes immigrants, refugees, business people, diplomats, foreign workers and students. The increasing number of a specific group in another country poses the importance of cross-cultural adaptation. Foreign student communities are a specific group of individuals that generally spend a few years in another country. In the new environment, cultural differences play a pivotal role in cross-cultural adaptation. There are many factors such as emotional intelligence which may affect cultural adaptation. Therefore, this study aims to investigate the role of emotional intelligence in cross-cultural adaptation amongst Iranian students in Malaysia. It also hopes that provided literature of this article will encourage theoretical and empirical work in the area of cross-cultural adaptation.